Obesity Among Athletes: An Analysis of Contributing Factors and Impact on Sports Performance - Uzair Ahmed Soomro; Soniha Aslam (The Sky)
This study investigates the complex relationship between obesity and athletic performance among athletes in the district of Shikarpur, with the aim of identifying underlying causes, assessing performance-related consequences, and exploring strategies to mitigate these effects. Using a qualitative approach supported by descriptive survey data from 50 athletes, the research examined lifestyle factors, injury-related inactivity, and psychological pressures as primary contributors to obesity within this population. The findings reveal that a significant proportion of athletes were overweight (32%) or obese (10%), with reported adverse impacts on endurance, strength, agility, and overall performance. Additional observations highlighted patterns such as late sleeping habits, prolonged use of high-tech devices, and mixed dietary behaviors, all of which may exacerbate weight management challenges. The discussion emphasizes that obesity among athletes extends beyond health concerns to directly impair critical sport-specific abilities. Effective interventions—such as nutrition education, injury prevention strategies, mental health support, and sport-specific training programs—are essential to address these challenges. This study contributes to a deeper understanding of the multifaceted nature of obesity in athletic contexts and underscores the need for integrated, evidence-based strategies to enhance both athletic performance and long-term health outcomes.